PREMATURE GRAYING OF HAIRS IN PATIENTS OF SCHIZOPHRENIA SPECTRUM DISORDER, AN INCIDENTAL FINDING OR SOME ASSOCIATION BETWEEN THESE TWO ENTITIES: A CASE SERIES. - Agarwal, Shikha; Yadav, Narveer; Yadav, Aarti; Charan, Deepak; Srivastava, Akash (Student’s Journal of Health Research Africa, 2024)
Introduction: Healthy hair is a sign of general well-being and youth. This case series addresses the unique occurrence of premature graying of hair (PGH) in patients diagnosed with schizophrenia spectrum disorder. PGH is perceived as a prominent sign of aging, driven by oxidative stress, which may indicate underlying systemic oxidative stress and be associated with various progressive systemic illnesses, including neuropsychiatric disorders. Case Presentation: In this case series, 14 young individuals (aged 18-25 years) exhibited heterogeneous behavioral symptoms suggestive of schizophrenia spectrum disorder alongside premature graying of hair. Behavioral symptoms included social withdrawal, unprovoked anger outbursts, auditory hallucinations, and significant socio-occupational dysfunction. Additionally, some cases had a family history of psychotic disorders or past medical conditions such as seizure disorders. Result: Patients were diagnosed with schizophrenia spectrum disorder by a dermatologist after excluding other cutaneous and systemic causes of graying. Behavioral changes varied in duration but commonly led to socio-occupational dysfunction, prompting medical attention. The onset of PGH ranged from simultaneous to before or after the behavioral disturbances, suggesting a possible timeline of progression linked to oxidative stress. Conclusion: Oxidative stress appears to be a common factor in both schizophrenia spectrum disorder and premature graying of hair, potentially serving as an early indicator of schizophrenia. Early intervention targeting oxidative stress and inflammatory markers, along with current therapeutic measures, may improve prognosis. Premature graying of hair could be considered a red flag for future schizophrenia transition, warranting further research to validate this association and explore preventive measures.